Representasi Islam dan Muslim dalam Media Berita India: Analisis Wacana Kritis Berbantuan Korpus - Oktaviani, Fatmala Sari (Kementerian Sekretariat Negara Republik Indonesia, 2023)
This study combines critical discourse analysis and corpus linguistics to explore how Islam and Muslims are portrayed in Indian news media. The analysis involves a 602,588-word corpus from three major Indian English language newspapers covering a three-year period (January 1, 2019—December 31, 2022). The study employs collocation and concordance line analysis using Antconc software to identify key thematic categories. Among the notable findings, conflict and crime emerge as a prevalent theme, depicting Muslims, particularly men, as perpetrators in situations related to coercive religious conversion. Additionally, a significant focus on terrorism is evident, with Islam often simplistically associated with acts of terror, contributing to the preservation of stereotypes. Moreover, the use of terms such as